2017
DOI: 10.1007/s10570-017-1435-2
|View full text |Cite
|
Sign up to set email alerts
|

In-situ synthesised hydroxyapatite-loaded films based on cellulose nanofibrils for phenol removal from wastewater

Abstract: Phenol removal from aqueous medium was studied by the batch method using novel and fully biobased solvent-cast films prepared from cellulose nanofibrils (CNFs) and in situ synthesised hydroxyapatite (HAp) by the wet-chemical precipitation method and different concentrations of HAp precursors and weight mass of CNFs. The chemical and morphological structures of as-prepared films were investigated by X-ray diffraction, scanning electron microscopy, and energy-dispersive spectroscopy, while their physical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 58 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…It can be seen that the peak intensity of O-H and C-H groups were decreased as shown in Fig. 3 (S4, S5, and S6), probably due to the interaction of these groups with HAp, which helped in attaching HAp on the surface of CNCs (Narwade et al 2017).…”
Section: Ftir Analysismentioning
confidence: 85%
See 1 more Smart Citation
“…It can be seen that the peak intensity of O-H and C-H groups were decreased as shown in Fig. 3 (S4, S5, and S6), probably due to the interaction of these groups with HAp, which helped in attaching HAp on the surface of CNCs (Narwade et al 2017).…”
Section: Ftir Analysismentioning
confidence: 85%
“…The FTIR spectra of Luffa bers (S1) and oxidized-nanocellulose (S3) samples exhibited a new absorption peak at 1733 cm -1 , resulted from the introduction of C=O group after H 2 O 2 treatment (Oun and Rhim 2018).The characteristic peaks of HAp which loaded on the surface of Luffa samples were detected at 1026 cm -1 due to PO4 3-group stretching mode ( 3, 1) and at 871 cm -1 correspond to 1 CO 3 2-(Yu et al 2013). It can be seen that the peak intensity of O-H and C-H groups were decreased as shown in Fig.3(S4, S5, and S6), probably due to the interaction of these groups with HAp, which helped in attaching HAp on the surface of CNCs(Narwade et al 2017).…”
mentioning
confidence: 85%
“…In industrial production, typical dyes, such as methyl orange and phenol red, have been applied widely. Cellulose and CNF-based materials have been synthesized to adsorb and remove these dyes [ 92 , 93 , 94 , 95 ]. For instance, Hasanpour et al reported the synthesis of cellulose/ZnO hybrid aerogels for the efficient removal of methyl orange, and the removal efficiency could reach 99.02% after 90 min of treatment [ 93 ].…”
Section: Environmental Science Applicationsmentioning
confidence: 99%
“…For instance, Hasanpour et al reported the synthesis of cellulose/ZnO hybrid aerogels for the efficient removal of methyl orange, and the removal efficiency could reach 99.02% after 90 min of treatment [ 93 ]. Narwade and co-workers demonstrated the in situ synthesis of CNF/hydroxyapatite hybrid films for the removal of phenol from wastewater [ 95 ]. The removal amount of phenol from acidic and neutral solutions was about 64 and 30 mg/g, respectively.…”
Section: Environmental Science Applicationsmentioning
confidence: 99%
“…The precipitation was carried out by the drop-wise addition of 0.6 M di-ammonium hydrogen phosphate into 1 M calcium nitrate tetrahydrate solution, under constant stirring of 150 rpm at 80 C for 4 h, followed by aging for about 24 h. The white precipitates were then washed 3-4 times with milliQ water to remove the rest of the precursors, and dried in a hot air oven at 100 C. The dried sample was further annealed at 1000 C for phase formation. AFM and XRD analyses of the preparation phase were performed for checking crystalline nature and finding grain size [52,53,54,55,56,57].…”
Section: Synthesis Of Nano Hydroxyapatite Bioceramic (Nano Hap)mentioning
confidence: 99%